h - Catalano, Dario; Fazio, Nelly; Gennaro, Rosario; Nicolosi, Antonio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed proceedings of the 14th International Conference on Practice and Theory in Public Key Cryptography, PKC 2011, held in Taormina, Italy, in March 2011. The 28 papers presented were carefully reviewed and selected from 103 submissions. The book also contains one invited talk. The papers are grouped in topical sections on signatures, attribute based encryption, number theory, protocols, chosen-ciphertext security, encryption, zero-knowledge, and cryptanalysis.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computational complexity; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Systems and Data Security; Discrete Mathematics in Computer Science